2012
DOI: 10.1614/ipsm-d-12-00039.1
|View full text |Cite
|
Sign up to set email alerts
|

Road Survey of the Invasive Tree-of-Heaven (Ailanthus altissima) in Virginia

Abstract: Tree-of-heaven is an invasive, nonnative species that invades newly disturbed areas and forms large monospecific stands. It was surveyed from a vehicle along 5,175 km of roads in Virginia in 2004, 2005, 2010, and 2011. Fifty-eight percent of every 1.6-km road segment had at least one tree-of-heaven. Mean density of tree-of-heaven throughout the roads surveyed in Virginia was 39 km−1. The interaction between road classification (interstate, primary, and secondary) and physiographic region (mountain, piedmont, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Invasive species biological recording, mapping, and monitoring are prerequisites for successful biological invasion risk management [31][32][33] and to prevent invasive species expansion into large areas, where eradication becomes very difficult and costly [1]. Among invasive plants, trees are generally easiest to map because of their size [34], although there is currently no methodical, reasonably priced protocol for the estimation of tree invasions that can be used in invasive species management or scientific research [35].…”
Section: Case Study-biological Recording Of Ailanthus Altissimamentioning
confidence: 99%
“…Invasive species biological recording, mapping, and monitoring are prerequisites for successful biological invasion risk management [31][32][33] and to prevent invasive species expansion into large areas, where eradication becomes very difficult and costly [1]. Among invasive plants, trees are generally easiest to map because of their size [34], although there is currently no methodical, reasonably priced protocol for the estimation of tree invasions that can be used in invasive species management or scientific research [35].…”
Section: Case Study-biological Recording Of Ailanthus Altissimamentioning
confidence: 99%
“…Even root fragments 1-cm long and a few mm wide are able to produce new suckers (Inverso & Bellani, 1991). In addition, main highways and railways, where Ailanthus commonly occurs, may act as a substantial source of seed to neighbouring natural and semi-natural areas, thus increasing its rate of spread (Aldrich et al, 2010;McAvoy, Snyder, Johnson, Salom, & Kok, 2012). Furthermore, in invaded environments, Ailanthus releases allelopathic compounds that may affect competitive dynamics with the native co-occurring species, especially during the seedling stage (Gómez-Aparicio & Canham, 2008), when competition for resources is generally higher.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have shown that nonmanaged forested areas, in particular, are thought to be important season-long reservoirs for dispersal of H. halys to agricultural crops (Bakken et al 2015). In Virginia, we have observed particularly high densities of H. halys on the invasive tree of heaven, Ailanthus altissima Mill., which has become the most dominant tree species along the edges of forests and roadways in Virginia (McAvoy et al 2012). Moreover, based on annual surveys of soybeans across Virginia from 2011 to 2012, the soybean fields having highest H. halys pest pressure were typically bordered by woods containing A. altissima.…”
mentioning
confidence: 99%